Avaliação das áreas de conflito de uso em APP na microbacia Ribeirão do Veado, Piratininga (SP) por meio de geotecnologias - Felipe, Andrea Cardador [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The present study aimed to analyze Ribeirão do Veado Watershed, located in the municipality of Piratininga / SP, mapping the types of use and land cover and their conflicts in the Areas of Permanent Preservation (APPs) in an interval of 39 years, through aerial photographs from 1972 and satellite image Landsat-5 2011. The study area is located geographically between the coordinates 49º06'33 to 49º09'54 W longitude Gr. and 22º23'24 to 22º26'07 S latitude, presenting an area of 1831,27ha. For this study, we used the planialtimetric letter of Bauru (SF-22-ZBI-4) in digital format, published by the Brazilian Institute of Geography and Statistics - IBGE (1973) in scale 1: 50000. The satellite image, bands 3, 4 and 5 of Landsat - 5, Sensor TM (Thematic Mapper), to June 22, 2011, orbit 221, paragraph 75, with spatial resolution of 30 x 30 meters, provided by the National Institute for Space Research (INPE). The Geographic Information System (GIS) used was Idrisi Selva, and the software, CartaLinx. The environmental legislation was the basis for the correct verification of the APPs along the drain and sources. The results of the mapping of the areas of use and land cover totalized ten classes of use in 1972, and pasture showed the largest occupation, with 68.07% of the total area. The mapping of 2011 showed eleven classes of use, demonstrating pasture as the highest land cover, with 57.96% of the area, confirming that the region has intense activity in cattle. The conflict maps of use of the land of 1972 and 2011 showed results that prove that the man is interfering with the natural landscape, even observing the increase of the forest from 11.46% to 30.28%, they are not being preserved enough, and most of the areas considered of Permanent Preservation (APP), according to Federal Law No. 12,651 / 12, are undocumented, even knowing they are critical to the ecological balance and the right water ...

O presente trabalho teve como objetivo analisar a microbacia Ribeirão do Veado, localizada no município de Piratininga/SP, mapeando as classes de uso e ocupação do solo e seus respectivos conflitos nas Áreas de Preservação Permanentes (APPs), num intervalo de 39 anos, por meio de fotografias aéreas de 1972 e imagem de satélite Landsat-5 de 2011. A área de estudo localiza-se geograficamente entre as coordenadas 49º06’33” a 49º09’54” de longitude W Gr. e 22º23’24” a 22º26’07” de latitude S, apresentando uma área de 1831,27ha. Para a realização dessa pesquisa, utilizou-se a carta planialtimétrica de Bauru (SF-22-Z-B-I-4) em formato digital, editada pelo Instituto Brasileiro de Geografia e Estatística - IBGE (1973) em escala 1:50000. A imagem de satélite, bandas 3, 4 e 5 do satélite Landsat - 5, sensor TM (Thematic Mapper), de 22 de junho de 2011, órbita 221, ponto 75, com resolução espacial de 30 x 30 metros, cedidas pelo Instituto Nacional de Pesquisas Espaciais (INPE). O Sistema de Informações Geográficas (SIG) utilizado foi o Idrisi Selva e o software, o CartaLinx. A Legislação Ambiental foi a base para a verificação correta das APPs ao longo da drenagem e das ...
Evaluation of the use of conflict areas in app in the watershed Ribeirão do Veado, Piratininga (SP) by geotechnologies
Keywords: Microbacias Hidrográficas; Monitoramento ambiental; Área de preservação permanente; Sistemas de informação geografica; Environmental quality